2014
DOI: 10.1002/pen.23956
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polystyrene‐grafted attapulgite via surface‐initiated redox polymerization

Abstract: Polystyrene‐grafted attapulgite (ATP‐g‐PS) was prepared using surface‐initiated redox initiation via graft from approach. ATP was modified with (3‐aminopropyl) triethoxysilane (APTES) to anchor amine on the surface (ATP‐NH2), and then ATP‐NH2 was further treated with 4‐(diethylamino) salicylaldehyde (DEAS) to give aromatic tertiary amine groups functional ATP (ATP‐ATA). Subsequently, the surface‐initiated redox polymerization of styrene in the presence of ATP‐ATA and benzoyl peroxide (BPO) was performed to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Variation of conversion, PG and GE with time is listed in Table . It can be found that PG and GE increase with polymerization time, and the highest experimental value of GE is approximately 51.3% in comparison with 21.2% in the research we have reported previously . Graft polymerization can contribute to the increase of PG substantially, even though the polymer grafting rate is smaller due to the relatively low concentration of the surface reactive sites.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…Variation of conversion, PG and GE with time is listed in Table . It can be found that PG and GE increase with polymerization time, and the highest experimental value of GE is approximately 51.3% in comparison with 21.2% in the research we have reported previously . Graft polymerization can contribute to the increase of PG substantially, even though the polymer grafting rate is smaller due to the relatively low concentration of the surface reactive sites.…”
Section: Resultsmentioning
confidence: 45%
“…Recently, we have reported the results of our research on the surface modification of ATP by graft polymerization via aliphatic amine‐ammonium persulfate, aromatic tertiary amine‐benzoyl peroxide redox system, and thiol‐caprolactam two‐component iniferter system . In this work, ATP was firstly modified to bear thiol groups, and then polydimethylaminoethyl methacrylate (PDMAEMA) was grafted from the surface of ATP by using a thiol‐Ce (IV) initiation system.…”
Section: Introductionmentioning
confidence: 99%
“…The PS chip surface will be surface-amine functionalized by APTES solution, which is beneficial to the subsequent encapsulation. Thirdly, both of the PS chip and silicone film should be modified by plasma oxidation [14]. Finally, the PS chip should be attached to the silicone film.…”
Section: Hot Embossing and Irreversible Bonding Of Ps Chipmentioning
confidence: 99%
“…Redox grafting has potential applications in membranes or in more exotic post-modified materials [285][286][287][288][289][290][291]. The synthesis of block copolymers via a redox polymerization process was reviewed by Ozturk et al a decade ago [293,294].…”
Section: Redox Graft Polymerization and Block Copolymerizationmentioning
confidence: 99%